2014
DOI: 10.1080/02640414.2014.918644
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of habitual physical activity level and weight status from fundamental movement skill level

Abstract: Fundamental movement skills (FMS) have been assessed in children in order to investigate the issues of the low proportion of children who meet physical activity (PA) guidelines and rising levels of obesity. The aim of this research was to identify whether previous or current FMS level is a better predictor of PA levels and weight status in children. In January 2012 (year 1), 281 children were recruited from one primary school in the West Midlands, UK. Children performed eight FMS three times, which were videoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(72 citation statements)
references
References 41 publications
8
64
0
Order By: Relevance
“…When MVPA was reallocated to sleep, ST, or LPA around the mean overweight/obese composition, the differences in predicted zBMI, %WHtR, and CRF were more than double those observed for reallocations at the mean composition for normal-weight children. Overweight/obese children typically have lower CRF [66], motor competence [67, 68], physical self-perceptions [69, 70], and are less physically active than leaner peers [71, 72]. Our results demonstrate that from a health perspective this group have most to lose when their activity behaviours are replaced with less intense or sedentary ones.…”
Section: Discussionmentioning
confidence: 76%
“…When MVPA was reallocated to sleep, ST, or LPA around the mean overweight/obese composition, the differences in predicted zBMI, %WHtR, and CRF were more than double those observed for reallocations at the mean composition for normal-weight children. Overweight/obese children typically have lower CRF [66], motor competence [67, 68], physical self-perceptions [69, 70], and are less physically active than leaner peers [71, 72]. Our results demonstrate that from a health perspective this group have most to lose when their activity behaviours are replaced with less intense or sedentary ones.…”
Section: Discussionmentioning
confidence: 76%
“…14 It has been proposed that FMS, PA, and BMI are related variables within child and adolescent populations. 4,10,15,16 A developmental perspective on the role of motor skill competence in PA presented by Stodden et al (2008) is a widely utilized framework to explain these relationships. In this conceptual model, Stodden et al (2008) highlight that there is a dynamic and reciprocal relationship between obesity, PA, motor skill competency, perceived motor competence, and physical fitness.…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have demonstrated that FMS, PA, and BMI are shown to be significantly correlated based on assessments undertaken during childhood and adolescence. [15][16][17] More specifically, research has indicated a negative relationship between FMS and being overweight, 16,17 and a positive relationship between FMS and a healthy weight status within child and adolescent cohorts. 15 Physical activity, motor competency, and cardiorespiratory fitness collectively have also been shown to have a strong longitudinal impact on the body fat levels of children.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quite consistently, significant predictors of PA are found within various individual, physical, social, and environmental realms. Individual predictors of PA include demographic and biological factors (e.g., age, gender, race/ethnicity); cognitive, psychological, and emotional factors (e.g., attitude, knowledge, level of motivation, self-esteem, self-efficacy, personality factors, intelligence, maturation level); and behavioral attributes (e.g., sedentary time; Biddle & Asare, 2011;Bryant, James, Birch, & Duncan, 2014;Colley et al, 2012;Hall, Fong, & Epp, 2014;Lowry, Lee, Fulton, Demissie, & Kann, 2013;Shokrvash et al, 2012). Predictors within the physical dimension include nutrition, smoking, alcohol use, drug use, and violence (Erker & Licen, 2012;Leggett, Irwin, Griffith, Xue, & Fradette, 2011).…”
Section: Introductionmentioning
confidence: 99%